Cardiac arrhythmias in a patient with severe whooping cough in the first year of life (clinical case) - S. N. Chuprova; I. V. Babachenko (Журнал инфектологии)
Whooping cough continues to lead in the group of vaccine-controlled infectious diseases. It is proved that in infants (especially in the first three months of life) patients more often endure severe forms of whooping cough with the development of complications, including apnea and pulmonary hypertension. There are few studies analyzing heart rhythm disorders in children with whooping cough and their relationship to the severity of the disease. The article presents a clinical case of a patient with severe whooping cough of the first year of life. Despite the absence of leukocytosis characteristic of severe whooping cough, the child’s condition was considered as severe due to episodes of apnea accompanied by desaturation and asystole. Detection of heart rhythm disorders in children with whooping cough is important in determining the tactics of their treatment and the need for further observation by a cardiologist.